Tree Cache - Anderson, Kenneth (Proceedings of the International Symposium on Combinatorial Search, 2012)
This program generates a single search tree, compacts it to reduce memory/disk space, then utilizes it to very quickly generate valid paths in an 8-connected gridworld. This technique is similar in principle to RRTs used in robotics.